A Study Of Compensation Strategy For Automated Test Equipment(ATE) Company - Khew, Loong Sang (2008)
The main objective of this study is to evaluate the current compensation package of key executive (CEOs) for ATE companies specifically and to recommend a general compensation package for key executive in companies operating in a high technology environment.